(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
In recent years, there has been a growing emphasis on researching quality of life, particularly within families that include members with disabilities. Family Quality of Life (FQOL) has gained prominence in special education as researchers seek to understand and improve the well-being of these families. This study aims to present findings on the quality of life of parents raising children with disabilities. Using a quantitative research approach and the validated BCFQOL tool, we surveyed 205 parents. The results were unexpectedly positive, showing generally higher levels of quality of life among participants. However, challenges were identified in specific dimensions such as “Emotional well-being,” and “Material well-being”.